Microstructure of concrete with aggregates from construction and demolition waste recycling plants - Bravo, M. (2017)
This paper intends to analyze the microstructure of concrete with recycled aggregates (RA) from construction and demolition waste from various Portuguese recycling plants. To that effect, several scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analyses were performed. Various concrete mixes were evaluated in order to analyze the influence of the RA’s collection point and consequently of their composition on the mixes’ characteristics. Afterward all the mixes were subjected to the capillary water absorption test in order to quantitatively evaluate their porosity. Results from the SEM/EDS analysis were compared with those from capillary water absorption test. The SEM/EDS analysis showed that the bond capacity of aggregates to the new cement paste is greatly influenced by the RA’s nature. On the other hand, there was an increase in porosity with the incorporation of RA.